Does the household clean energy transition benefit the mental health of the elderly in rural China? Evidence from China health and retirement longitudinal study - Hengxing Yin; Ling Han; Li Yan; Chenhao Liu (Environment International)
Clean energy transition has become a key strategy in combating global air pollution. In 2017, China launched its “coal-to-gas” policy, which provided subsidies to households for their clean energy transition. While debates on this policy focus mainly on safety and cost concerns, few studies have examined the causal relationship between energy transition and its health benefits, particularly mental health. Using data from the China Health and Retirement Longitudinal Survey (CHARLS), this paper employs a difference-in-differences (DID) approach to estimate the impact of the “coal-to-gas” policy on the mental health of the rural elderly in China. The findings indicate that the policy significantly improved the cognitive status of the elderly, especially episodic memory, which saw a 10.4% increase relative to the sample mean. The policy also significantly boosted the proportion of households using clean cooking fuels by 5.8%. Further analysis suggests that the improved sleep quality from reduced indoor air pollution by household energy transition, as a mechanism, could explain these results. This study provides a timely assessment of the policy’s effectiveness, highlighting the importance of indoor air pollution control by household energy transition.